A practical guide to developing virtual and augmented reality exercises for teaching structural biology1. Issue 1 (26th November 2018) - Garcia‐Bonete, Maria‐Jose; Jensen, Maja; Katona, Gergely
Abstract: Although virtual and augmented reality (VR and AR) techniques have been used extensively in specialized laboratories, only recently did they become affordable, reaching wider consumer markets. With increased availability, it is timely to examine the roles that VR and AR may play in teaching structural biology and in experiencing complex data sets such as macromolecular structures. This guide is suitable for those teachers of structural biology who do not have a deep knowledge of information technologies. This study focuses on three questions: 1) How can teachers of structural biology produce and disseminate VR/AR‐ready educational material with established and user‐friendly software tools?; 2) What are the positive and negative experiences reported by test participants when performing identical learning tasks in the VR and AR environments?; and 3) How do the test participants perceive prerecorded narration during VR/AR exploration? © 2018 International Union of Biochemistry and Molecular Biology, 47(1):16–24, 2018.